The Significance of The Difference Between Traditional and Tunnel Method for Salt Production in Tuban, East Java, Indonesia - M. I. Syafii; A. A. Amin; A. A. Jaziri; W. Setiawan; A. A. Prihanto (Future Science)
Salt is an important material for industrial point of view. It is not only used in food industry, but also applied in wide range of industries. Indonesia government had the priority program in the field of food sovereignty targeting salt production around 3.6 million ton in 2017, main problem of salt production in Indonesia is low productivity and quality because the technology used commonly by Indonesian salt farmers is traditional method. The productivity of the traditionally salt production is 30-50 tons/ha with the low quality of salt around 80% of NaCl. This research aims to increase production of salt by using the tunnel method. The tunnel method is a salt production system with a combination of several salt production technologies, including geomembrane, uv plastic with trapping hit. This research method used descriptive method. The results of this study were the productivity of the tunnel is 80 –100 tons/ha with NaCl content is around 93%, and the magnesium (Mg) content is around 2.46 mg/liter with high quality. In addition, salt production with the tunnel method has several advantages, such as faster harvest time, weather resistance, easy to use, and higher profit than traditional methods.